Cold snare polypectomy vs. hot snare polypectomy vs. argon plasma coagulation for small (5–9mm) left-sided colorectal polyps: a prospective randomized trial. Issue Volume 33:Issue S1(2021) (29th October 2021) - Varytimiadis, Lazaros; Viazis, Nikos; Gkolfakis, Paraskevas; Tribonias, Georgios; Tziatzios, Georgios; Kyriakopoulos, Georgios; Argyrakos, Theodore; Pontas, Christos; Papastergiou, Vasilios; Arkadopoulos, Nikolaos; Smyrniotis, Vasilios; Mantzaris, Gerassimos J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: To compare recurrence rates among three endoscopic treatment modalities for 5–9 mm left-sided colorectal polyps. Methods: Consecutive adults referred for elective colonoscopy (1/2015–1/2018) with at least one polyp of eligible size (5–9 mm) located distally to the splenic flexure were randomly assigned (1:1:1) to one of three treatment modalities: (1) cold snare polypectomy (CSP), (2) hot snare polypectomy (HSP) and (3) argon plasma coagulation (APC) ablation (50–60 W, flow: 2 l/min). The polyp site was marked with an endoscopic tattoo, and a follow-up colonoscopy with scar biopsies was performed >6 months after the index procedure. Outcomes were polyp recurrence rate and occurrence of complications. Results: One hundred nineteen patients were enrolled, of whom 112 (62.5% males, mean age 61.1 ± 9.9 years) with 121 polyps (CSP, 39; HSP, 45; APC, 37) returned for follow-up colonoscopy. Mean polyp size was 6.7 ± 0.91 mm, 58% were located in the sigmoid, 33% in the rectum and 8% in the descending colon. The majority of polyps resected by CSP or HSP were neoplastic (tubular adenomas: 25.9%, tubulovillous adenomas: 11.1% and sessile serrate adenomas/polyps: 17.5%). No cases of delayed bleeding or perforation occurred. Scar biopsies at follow-up colonoscopy (performed after a mean interval of 13.4 ± 3.8 months) revealed 7 (5.8%) cases of polyp recurrence, showing no significant difference among the three treatment groups [CSP, 3/39 (7.7%); HSP, 1/45 (2.2%); APC, 2/37 (5.4%); P  = 0.51). Conclusions: CSP, HSP and APC-ablation are effective and well-tolerated treatment modalities for 5–9 mm left-sided colorectal polyps. The present randomized study did not detect any difference in polyp recurrence rate among the three endoscopic techniques.